Seismic hazard zoning in Urmia urban area. - Ali nasiri (تحقیقات کاربردی علوم جغرافیایی)
Today, the resiliency of the human centers, especially urban centers against the natural hazards such as earthquakes, is one of the main challenges in the targeted management of urban. One of the effective strategies in the control, containment and prevention of risks from earthquakes is zoning of urban areas in terms of vulnerability. In this regard, the purpose of this study was to determine the zoning and seismic active zones in the urban area of Urmia city. The seismic – tectonic situation and recorded seismic data  surveyed in the current study. findings showed that there were seismic active zones in the Uremia city area. The seismic effects and geo-tectonic results Verified, so the results marked that local geology condition would be effective in earth motion. This research investigated the local geology features especially fault, geo units and seismic data in zoning of seismic risk. Many methods are proposed by different researchers. In this study the SABTA (1987) method has been used for estimating seismic risk by using most important parameters such as seismic, fault and geology data. The obtained results showed that the P.G.A measure variation was from 0.035 to 0.33 which indicated the existence of seismic activity in the study area.